Elementary School Social Emotional Learning Status and Attendance, Discipline, and Achievement in the United States: A National Analysis - Morris, Oleavia Shaunté; Lunenburg, Fred C.; Slate, John R; Hemmen, Janene (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2023)
Ascertained in this investigation was the effect of social emotional learning training on student attendance, discipline problems and actions, students’ thoughts on the importance of academic achievement, and urbanicity in public elementary schools for the 2015-2016 and 2017-2018 school years. We analyzed data from two School Surveys on Crime and Safety conducted across the United States. Across the two years, social emotional learning training was determined to be unrelated to public elementary schools’ location (i.e., urban, suburban, rural), student attendance or discipline problems and actions. The presence of social emotional learning training, however, was determined to be related to the importance of academic achievement. Implications for policy and for practice, along with recommendations for future research, were made.